2017
DOI: 10.2147/prbm.s125176
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences and psychological factors associated with suicidal ideation among youth in Malaysia

Abstract: Suicide is a global phenomenon that has been showing an upward trend in recent years. It is the second leading cause of death among youth. Studies on suicidal ideation warrant greater attention, as it leads to suicide attempts and other health risk behaviors. Thus, the objective of this study was to compare gender differences in suicidal ideation and determine the predictors of suicidal ideation among youth. This cross-sectional study was carried out among 232 youths aged between 15 and 25 years from selected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
28
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(33 citation statements)
references
References 57 publications
4
28
0
1
Order By: Relevance
“…Suicidal ideation among undergraduates is associated with various factors. Among the demographic factors, our findings are consistent with previous studies where females were more prone to suicidal ideation [61][62][63][64][65]. However, undergraduates who major in the liberal arts are more likely to experience suicidal ideation than those in medicine.…”
Section: Discussionsupporting
confidence: 91%
“…Suicidal ideation among undergraduates is associated with various factors. Among the demographic factors, our findings are consistent with previous studies where females were more prone to suicidal ideation [61][62][63][64][65]. However, undergraduates who major in the liberal arts are more likely to experience suicidal ideation than those in medicine.…”
Section: Discussionsupporting
confidence: 91%
“…A previous study conducted in South Korea revealed that the prevalence of suicidal ideation was higher among female adolescents than among their male counterparts [24]. Another study conducted in Malaysia showed that suicidal ideation was higher among males compared with females [25]. Similarly, a study from China mainland showed that girls were significantly more likely than boys to report both suicidal ideation and attempts [26].…”
mentioning
confidence: 92%
“…Gender-related aspects also seem to influence or mediate the drug use profile and the severity of crack-cocaine dependence [22,23] and may be potentially associated with suicide [3,[24][25][26]. Although some predictors of suicide are common to both genders, such as prior mental disorders, substance abuse, and early exposure to violence, some other potential risk factors appear to be gender-specific [26].…”
Section: Introductionmentioning
confidence: 99%